AB0140 Investigation of joint regeneration mechanisms in NEWTS (notophthalmus viridescens). (23rd January 2014) - Susanto, S.A.; Schreiyäck, C.; Geyer, M.; Borchardt, T.; Müller-Ladner, U.; Dinser, R.M.
Abstract : Background: The adult red-spotted newt ( notophthalmus viridescens ) is able to regenerate damaged knee joints after local injury involving surgically induced defects, and collagenase induced joint instability. The mechanism behind this capacity that lacks in mammals is currently not understood. Objectives: Investigating the molecular process of joint regeneration in newts and deducing the potential gene candidate Methods: Transcriptome analysis with cDNA array derived from regenerating newt myocardium was carried out after surgical and collagenase, induced knee damage. We validated the differentially expressed genes in both instances using qRT-PCR. We conducted immunohistochemistry (IHC)and in situ hybridization (ISH) to investigate spatial distribution of the most promising deregulated genes. Results: 88 from 260 significantly regulated gene transcripts had homology to gene transcripts in public DNA database. We selected the deregulated genes retinoic acid receptor response element 3 (RARR), periostin, tenascin-C (TN-C), olfactomedin, osteonektin, decorin, gamma B crystalline (GBC), thymosin β 4 and complement factor B for further analysis after qPCR-confirmation of deregulation. Tenascin C, the most upregulated gene, locates to the periosteum and perichondrium in newts and is additionally strongly expressed in the undifferentiated regeneration tissue after joint injury. We are currently analyzing the other candidate genes. Conclusions: We found several gene candidates which may be central to the newts capacity for joint regeneration by employing cDNA array derived from regenerating newt myocardium. TN-C may be an important mediator of joint formation. References: Matthias Geyer, Thilo Borchardt, Carina Schreiyäck, et al. Endogenous regenration after collagenase -induced knee joint damage in the adult newt notophthalmus viridescens. Ann Rheum Dis (2010). doi:10.1136/ard.2009.126136. James W. Godwin, Jeremy P. Brockes. Regeneration, tissue injury and the immune response. J. Anat. (2006) 209: 423-432 Thilo Borchardt, Mario Looso, Marc Bruckskotten, et al. Analysis of newly established EST databases reveals similarity between heart regeneration in newt and fish. BMC Genomic (2010): 11:4 Disclosure of Interest: None Declared